Weak, Permissive and Error-Tolerant Supervision: Starting From Correction Habits to Acquit et de Charge Trap As an Entrance to Capital Market Scandal - Shalahuddin Haikal (Asia Pacific Fraud Journal, 2019)
Indonesian financial sector supervision, including the Capital Market is done by the Otoritas Jasa Keuangan/OJK (Financial Services Authority). Capital market is a market driven by the coming of new information. The punctuality and accuration of information are the key for an efficient capital market. The OJK structure and internal process makes us understand why OJK is weak, slow, permissive and error-tolerant to erroneousness. This condition is exploited by issuers/listed companies, including, banking sector companies, ignoring the carefulness rules in delivering the disclosure obligation. It explicitly comes up from most of the correction and revision toward disclosures they have made or even not doing the disclosure obligation. Worse, the audited anual financial which have accepted and legalized by General Meeting of Shareholders and therefore receive acquit et de charge, is rectified for restatement reason. It seems that the OJK failed to understand and stutter against forms of non-compliance and old crime in the new structure, in the form of omission, for investors this failure was a form of impartiality to them. OJK should act as an investor’s advocate, not an issuer carer. In addition to the silo structure, there is an incompatibility of the investigation function with the provisions regarding the investigation in accordance with the Criminal Procedure Code and other deficiency.